Genetic Dissection of Quantitative Resistance to Common Rust (Puccinia sorghi) in Tropical Maize (Zea mays L.) by Combined Genome-Wide Association Study, Linkage Mapping, and Genomic Prediction - Ren, Jiaojiao; Li, Zhimin; Wu, Penghao; Zhang, Ao; Liu, Yubo; Hu, Guanghui; Cao, Shiliang; Qu, Jingtao; Dhliwayo, Thanda; Zheng, Hongjian; Olsen, Michael; Prasanna, Boddupalli M.; et al. (Frontiers in Plant Science, 2021)
Common rust is one of the major foliar diseases in maize, leading to significant grain yield losses and poor grain quality. To dissect the genetic architecture of common rust resistance, a genome-wide association study (GWAS) panel and a bi-parental doubled haploid (DH1) population were used to perform GWAS and linkage mapping analyses. GWAS results revealed six SNPs significantly associated with quantitative resistance of common rust at a very stringent threshold of P-value of 3.70×10-6 at bins of 1.05, 1.10, 3.04, 3.05, 4.08, and 10.04, respectively. Linkage mapping identified five quantitative trait loci (QTL) on chromosomes 1, 2, 4, 7, and 9. The phenotypic variation explained (PVE) value of each QTL ranged from 5.40% to 12.45%, accounting for the total PVE value of 40.67%. Joint GWAS and linkage mapping analyses identified two stable genomic regions located at bins 1.05 and 4.08, respectively. Four significant SNPs were only identified by GWAS and three QTL were only detected by linkage mapping. The significantly associated SNP of S10_95231291 detected in the GWAS analysis was firstly reported. Linkage mapping analysis detected two new QTL on chromosomes 2 and 7. The major QTL on chromosome 7 in the region between 144,585,945 and 149,528,489 bp, had the largest PVE value of 12.45%. Four candidate genes of GRMZM2G328500, GRMZM2G162250, GRMZM2G114893, and GRMZM2G138949, were identified, which played important roles in the response of stress resilience and the regulation of plant growth and development. GP accuracies observed in the GWAS panel and DH1 population were 0.61 and 0.51, respectively. This study provided new insight into the genetic architecture of quantitative resistance of common rust. In tropical maize, common rust could be improved by pyramiding the new sources of quantitative resistance through marker-assisted selection (MAS) or GS, rather than the implementation of MAS for the single dominant race-specific resistance gene.